An initial and boundary value problem of fractional Jeffreys' fluid in a porous half space. (15th September 2019) - Guo, Xiaoyi; Fu, Zunwei
Abstract: In this paper, the fractional calculus approach is employed in the constitutive relationship of the fluid model and the Darcy's law. The flow of the fractional Jeffreys' fluid induced by the impulsive motion of a flat plate in a porous half space is studied in form of an initial and boundary value problem with fractional derivatives. Using the Laplace transform method, we obtain an exact solution of the model in term of Fox's H -function. As a byproduct, the solutions of the analogous flow for the generalized second grade fluid, the fractional Maxwell fluid and the Newtonian fluid in the porous half space are also deduced. In addition, the influence of the material parameters and the fractional parameters on the fluid motion is investigated, as well as a comparison among the fractional Jeffreys' fluid, the fractional Maxwell fluid and the Newtonian fluid in porous medium is also analyzed by graphical illustrations.